Structural heterogeneity of milk casein micelles: a SANS contrast variation study. Issue 2 (12th November 2014) - Bouchoux, Antoine; Ventureira, Jorge; Gésan-Guiziou, Geneviève; Garnier-Lambrouin, Fabienne; Qu, Peng; Pasquier, Coralie; Pézennec, Stéphane; Schweins, Ralf; Cabane, Bernard
Abstract : SANS contrast variation suggests that milk casein micelles are core–shell particles in which the shell has a lower concentration of minerals than the core. Abstract : We examine the internal structure of milk casein micelles using the contrast variation method in Small-Angle Neutron Scattering (SANS). Experiments were performed with casein dispersions of different origins ( i.e., milk powder or fresh milk) and extended to very low q -values (∼9 × 10 −4 Å −1 ), thus making it possible to precisely determine the apparent gyration radius R g at each contrast. From the variation of I ( q → 0) with contrast, we determine the distribution of composition of all the particles in the dispersions. As expected, most of these particles are micelles, made of casein and calcium phosphate, with a narrow distribution in compositions. These micelles always coexist with a very small fraction of fat droplets, with sizes in the range of 20–400 nm. For the dispersions prepared from fresh milk, which were purified under particularly stringent conditions, the number ratio of fat droplets to casein micelles is as low as 1 to 10 6 . In that case, we are able to subtract from the total intensity the contribution of the fat droplets and in this way obtain the contribution of the micelles only. We then analyze the variation of this contribution with contrast using the approach pioneered by H. B. Stuhrmann. We model the casein micelle as a core–shell spherical object, in which the local scattering length density is determined by the ratio of calcium phosphate nanoclusters to proteins. We find that models in which the shell has a lower concentration of calcium phosphate than the core give a better agreement than models in which the shell has a higher density than the core.